Religious Investor Sentiment, Shariah Compliance Impact, and Theological Risk: Evidence from Bursa Malaysia - Murat Yaş; Mohamed Eskandar Shah Mohd Rasid; Ahmet Faruk Aysan; Saad Azmat (Türkiye İslam İktisadı Dergisi)
This study examines the financial implications of religious restrictions by analyzing how changes in the Shariah compliance status of stocks affect their price and trading volume. Employing the market model in an event study approach and using data from Malaysian firms between 2000 and 2016, the study focuses on 30 announcements from the Security Commission Malaysia’s List of Shariah Compliant Securities (LSCS), resulting in 370 additions and 284 deletions from the compliance list. The findings indicate that the inclusion of stocks in the compliance list generates longterm demand driven by Islamic institutional and Muslim retail investors, leading to a permanent increase in abnormal returns and trading volume. Conversely, the removal of stocks from the compliance list induces short-term negative abnormal returns and increased trading volume, reflecting selling pressure. These results contribute to understanding the financial consequences of religious restrictions, highlighting the influence of Shariah compliance on stock market performance and investor behaviour.